Hospitality Financial Management - Agnes L. DeFranco; Thomas W. Lattin (USA John Wiley & Sons, 2007)
Real-world advice for quick retention of the most importantbusiness concepts and skills of hospitality finance Hospitality Financial Management provides astraightforward, practical approach to help the hospitality managereffectively analyze hospitality industry management reports andfinancial statements; prepare accurate business forecasts,strategic pricing models, and effective cost-control systems;manage working capital; develop and finance growth strategies;perform investment analysis; prepare investment packages; negotiateand structure business deals; and ultimately increase shareholdervalue and personal wealth. This comprehensive how-to book includes: Hospitality Financial Management is the perfect book forundergraduate and graduate hospitality management students,hospitality industry managers, and owners of small hospitality businesses.
Age Group: Adult
Includes index.
Keywords: Hospitality industry; Finance; Nonfiction